THE RELATIONSHIP BETWEEN MATERIALISM AND FINANCIAL LITERACY ON STUDENT FINANCIAL MANAGEMENT BEHAVIOR - Adinda Tasya Salsabilla Anwar; Goso Goso; Sari Ratna Dewi (Sekolah Menengah Kejuruan (SMK) Pustek, 2023)
This study aims to determine the relationship between materialism and financial literacy on the financial management behavior of students of the management study program at the Faculty of Economics and Business, Muhammadiyah University of Palopo. The method used in this research is quantitative. The sample used in this study consisted of 85 respondents. Determination of the sample using purposeful sampling. This research method uses a quantitative approach. Data was collected using the method of distributing questionnaires via Google and analyzed using multiple linear regression analysis, a t-test (partial), and an F-test (simultaneous) using the IBM SPSS 25 application. The results of this study indicate that materialism has a positive and significant effect on student financial behavior. Meanwhile, financial literacy also has a significant influence on student financial management behavior. The conclusion in this study is that there is a relationship between materialism and financial literacy on the financial management behavior of students of the management study program at the Faculty of Economics and Business, Muhammadiyah University of Palopo.